A Divorce Lawsuit Based on the Husband’s Failure to Adequately Fulfill Financial Support Obligations: A Case Study of Decision Number 350/pdt. G/2024/MS. Bna - Retno Arimbi Dewi; Soraya Devy; Misran Ramli (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2025)
Marriage in Islam is a sacred bond (mitsaqan ghalidzan) that requires the husband to provide financial support to his wife, as regulated by Islamic law and Indonesian legislation. However, problems arise when the husband, despite being financially capable, is stingy in fulfilling this obligation, resulting in household disharmony and divorce. This study examines the legal implications of this attitude through a normative legal analysis of the Banda Aceh Sharia Court Decision Number 350/Pdt.G/2024/MS.Bna. The purpose of the study is to analyze the legal basis for providing support, the husband's stinginess as a reason for divorce, and the judge's considerations in deciding the case. Using a normative legal approach, the study uses primary data from court decisions and secondary data from existing theories and research. The results show that providing support is a husband's obligation based on Islamic law (the Qur'an, Hadith) and national law (Law No. 1/1974, KHI). Stinginess in providing support, even if the husband is in a sufficient economic condition, is considered a neglect of obligations and is a valid reason for divorce. The study's conclusion suggests that an Islamic legal perspective aligns with this issue, emphasizing justice and responsibility. It is recommended that future researchers conduct more in-depth comparative studies on the implementation of livelihood provisions in various regions with varying socioeconomic characteristics.